Dehydration of Suillus luteus mushroom at different drying temperature, drying method, and pretreatment - Chaquilla Quilca, Guadalupe (2026)
The aim of this research was to assess the influence of drying temperature, drying method, and pretreatment on the dehydration of the edible mushroom Suillus luteus, focusing on its physical, functional, and sensory characteristics. Suillus luteus were harvested from Soccllacasa, Apurímac-Peru. Two drying temperatures (50 and 70 °C), two drying methods (oven and vacuum), and two pretreatment techniques (1% citric acid and blanching) were employed. Mushroom slices were immersed in solutions and subsequently subjected to drying. Analytical parameters, including instrumental color, total polyphenol content, antioxidant capacity, Fourier Transform Infrared Spectroscopy (FTIR) analysis, and sensory evaluation using Flash Profile, were conducted. The findings revealed significant differences (p<0.05) among the treatments. Higher drying temperatures, vacuum drying, and blanching exhibited superior color attributes. Polyphenol content and antioxidant capacity decreased in the dried samples, confirmed by FTIR; however, treatments dried at elevated temperatures under vacuum, showed enhanced preservation of these compounds. Sensory analysis revealed the formation of four groups based on temperature and drying method, but not on pretreatment, samples dehydrated at 70 °C under vacuum showing superior sensory characteristics. Thus, it is recommended to dehydrate Suillus luteus at higher temperatures under vacuum, as they offer improved preservation quality and sensory acceptability.